2008
DOI: 10.1136/ip.2007.017947
|View full text |Cite
|
Sign up to set email alerts
|

Restraining orders among victims of intimate partner homicide

Abstract: Most female IPH victims did not have a restraining order when they were killed. Further research is needed to determine whether restraining orders protect against IPH and, if they do, on how to increase their utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 29 publications
2
20
0
1
Order By: Relevance
“…Despite this, studies have shown that many victims and perpetrators make disclosures and seek assistance for family violence-related issues (Brown and Hampson 2009; The National Council to Reduce Violence against Women and their Children [NCRVWC] 2009). The first point of service contact is most commonly the justice system, but also includes the healthcare system and community or specialist family violence services (Block 2008;Meyer 2010;Mouzos and Makkai 2004;Vittes and Sorenson 2008). The key components of the justice system response to family violence include police attendance following reported incidents of family violence; court issued family violence intervention orders (IVO); and prosecuting criminal offences arising from family violence.…”
mentioning
confidence: 99%
“…Despite this, studies have shown that many victims and perpetrators make disclosures and seek assistance for family violence-related issues (Brown and Hampson 2009; The National Council to Reduce Violence against Women and their Children [NCRVWC] 2009). The first point of service contact is most commonly the justice system, but also includes the healthcare system and community or specialist family violence services (Block 2008;Meyer 2010;Mouzos and Makkai 2004;Vittes and Sorenson 2008). The key components of the justice system response to family violence include police attendance following reported incidents of family violence; court issued family violence intervention orders (IVO); and prosecuting criminal offences arising from family violence.…”
mentioning
confidence: 99%
“…Latinas may be less likely than other racial/ethnic groups to reach out to police for domestic violence assistance because, for instance, the police may respond inappropriately and use children or perpetrators to translate (Erez & Hartley, ; Messing, Becerra, Ward‐Lasher, & Androff, ; Silva‐Martinez & Murty, ), which may increase the risk of retaliatory and potentially lethal male violence, and are less likely than other racial/ethnic groups to seek out restraining orders because, for instance, they may not know they are available (Messing, Vega, & Durfee, ; Reina et al, ) or rely on their abusers' income for survival (Reina & Lohman, ). However, Vittes and Sorenson's () study summarized below challenges these contentions. Additionally, Latina immigrants who are undocumented may be unaware that they are able to petition for restraining orders without risking deportation (Center for Relationship Abuse Awareness , n.d.; Messing et al, ), so may avoid this resource.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A long history of IPV has been associated with lethal violence victimization among women from various racial and ethnic groups, including Black Americans (Campbell et al, 2003; Vittes Sorenson, 2008). Men often kill their female partners after subjecting them to lengthy periods of coercive abuse and assaults (Aldridge, Browne, 2003).…”
Section: Abuse-related Characteristicsmentioning
confidence: 99%
“…Yet, research suggests a small proportion of women obtain restraining orders (Logan, Shannon, Walker, Faragher, 2006). Vittes and Sorenson (2008) reported most women did not have a restraining order when they were killed. Only 11% of 231 women killed by their intimate partners had been issued a restraining order.…”
Section: Use Of Community Resourcesmentioning
confidence: 99%
See 1 more Smart Citation